A vanG-type locus in Clostridium argentinense. (22nd March 2015) - Berthet, Nicolas; Périchon, Bruno; Mazuet, Christelle; Chapetón-Montes, Diana; Bouchier, Christiane; Bouvet, Philippe; Legeay, Christine; Popoff, Michel-Robert; Courvalin, Patrice
Abstract: Objectives: The objective was to study a new vanG -type locus in Clostridium argentinense vanGCar and to determine its impact on glycopeptide susceptibility of the host. Methods: The whole genome of C. argentinense NCIB 10714 was sequenced using Illumina single-reads sequencing technology. The presence of vanGCar in seven C. argentinense strains was tested by PCR and its expression was tested by quantitative RT–PCR (qRT–PCR). Glycopeptide susceptibility was determined by the Etest procedure. Results: The vanGCar locus contained four genes encoding a carboxypeptidase, a d -alanine:d -serine ligase, a serine transporter and a serine racemase, and was present in the seven C. argentinense studied. An AraC-type transcriptional regulator was found upstream from the genes. C. argentinense NCIB 10714 was susceptible to vancomycin and to teicoplanin. qRT–PCR experiments revealed that vanGCar was not expressed without or with induction by a subinhibitory concentration of vancomycin. Conclusions: The new vanGCar locus was cryptic in C. argentinense and intrinsic to this species. Emergence of vancomycin resistance in C. argentinense due to decryptification of the vanGCar gene cluster could occur.